An industrial impulse? Work and filmmaking tactics in Portuguese tourism films (1940-1970) - Sampaio, S. (The NECS 2018 Conference: Media Tactics and Engagement, 2018)
The study of tourism has been shaped by the dichotomy of work versus leisure, whereby tourism is normally conceived as an expression of the latter. As a result, tourism studies tend to turn a blind eye to work-related aspects, perceived to be the concern of more business-oriented studies. The traditional divide, in film studies, between textual and industry approaches has similarly encouraged a separate treatment of formal and production aspects of film. And yet the research I have been carrying out on Portuguese tourism films has made dichotomy-ridden approaches as these unsustainable. After a few archival viewings, the ‘hybridity’ of tourism films and their ‘contamination’ by industrial films became hard to ignore: long sequences of images showing industrial sites, workers and processes were fairly common amidst the usual picturesque views and overtly promotional displays of tourism infrastructures. The co-habitation of industry and tourism in these films can be convincingly attributed to the subordination of tourism to a state propaganda modernising agenda, which lasted well beyond the late 1960s, when tourism became a more autonomous activity. However, the interviews I conducted with filmmakers suggest that this mixture of genres was often also linked to filmmaking practices, reflecting, for instance, a filmmaker’s tactics to potentiate location shooting or to please different sponsors. This paper wishes to explore the ‘industrial contaminations’ of Portuguese tourism films made in 1940-1970, by drawing attention to the filmmaking production logics and practices in which these films were embedded. I have drawn inspiration from industrial film research (e.g. Hediger and Vonderau, 2009), which has been especially adroit in attending to and making sense of these logics and practices. I will ultimately argue that, even before being linked to a fully-fledged industry (i.e. tourism), tourism films can already be productively thought of as ‘industrial films’.